2015
DOI: 10.3390/ijerph121012988
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Active Commuting to School in Czech Adolescents in Different Types of Built Environment across a 10-Year Period

Abstract: Active commuting (AC) to school represents a great opportunity to incorporate walking or cycling into adolescents’ everyday routine. The objective of the study was to describe changes in AC in Czech adolescents across a 10-year period in different built environments. Data from the 2001 and 2011 Czech Census of Population and Housing were used to examine the mode of transportation taken to school in 6236 adolescents. Changes in AC over time were analyzed for low and high walkable areas separately in two Czech r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 37 publications
3
39
0
4
Order By: Relevance
“…Dygryn et al (28) confirmed the findings of previous international studies about decreasing levels of AC among children of school age in the Czech Republic between 2001 and 2011 and emphasizes the increasing number of adolescents using passive modes of transportation to school (city transport, bus, and as a car passenger).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Dygryn et al (28) confirmed the findings of previous international studies about decreasing levels of AC among children of school age in the Czech Republic between 2001 and 2011 and emphasizes the increasing number of adolescents using passive modes of transportation to school (city transport, bus, and as a car passenger).…”
Section: Introductionsupporting
confidence: 75%
“…Concurrently, another important factor influencing AC is associated with the characteristics of the building environment on the way to school (the presence of pavements, traffic safety, and the number of roads to cross) and may influence how parents choose to have their children commute from home to school (33,34). Moreover, the level of AC in school-aged children can be influenced by the location of the school and distance from the place of residence (12,20,28). These findings are important for policymakers aiming to maximize the use of active forms of transport (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Active travel (AT) is an important part of adolescents' everyday physical activity (PA). Nonetheless, we have been observing a long-term decreasing trend in AT throughout adolescence in many socioeconomically developed countries [1][2][3][4], but not in all of them [5]. The health, economic, social and behavioral benefits of AT are adequately supported by the research [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…Navzdory výhodám AD využilo tuto možnost v České republice v roce 2011 o 47 % méně ško-láků než v roce 2001 (Dygrýn, Mitáš, Gába, Rubín, & Frömel, 2015). Pro zlepšení propagace a zvýšení využití AD je důležité co nejlépe poznat, které faktory volbu AD ovlivňují.…”
Section: úVodunclassified